AN AUDIT OF MANAGEMENT OF ACUTE PANCREATITIS - Tariq Mahmood; Khalid Naseem (Journal of University Medical & Dental College)
ABSTRACT OBJECTIVE: To evaluate the clinical presentation in different age and gender groups ,risk factors and outcome of management of patients with acute pancreatitis in surgical unit of Aziz Fatima hospital. DESIGN: Prospective study. PLACE AND DURATION OF STUDY: Aziz Fatima surgical ward, February 2011 to March 2014. SUBJECT AND METHODS: Data was compiled for the above said period comparing age, occupation, gender and symptoms. Furthermore assessment of severity and differential outcomes in response to the conservative management along with applied surgical options were studied. CONCLUSION: There is no link between age, gender, etiology, and severity of symptoms in acute pancreatitis. Prediction for local or systemic complications is difﬁcult. Conventional conservative approach for the management of acute pancreatitis has got worth; temptations for early intervention should be resisted until unless there are deﬁnite indications for exploration.